Method Validation and Application of Curcumin UV–Vis Assay for Borax in Nuggets in Gorontalo, Indonesia - Ishak Isa; Muhammad Taupik; Paramita Musa; Mahdalena Sy. Pakaya; Wiwit Zuriati Uno (Indonesian Journal of Pharmaceutical Education, 2026)
Borax (sodium tetraborate decahydrate; Na₂B₄O₇·10H₂O) is prohibited for use in processed foods in Indonesia, necessitating analytically defensible surveillance methods for routine monitoring. This study aimed to validate a curcumin-based UV–Vis spectrophotometric assay and to apply rapid qualitative screening to nugget products marketed in Gorontalo, Indonesia. Qualitative screening was performed using the flame test and turmeric paper test on six samples (A1–C2) collected in October 2025. For the UV–Vis method, wavelength optimisation using a 500 µg/mL borax standard identified 427 nm as the operational measurement wavelength. Calibration standards (1–9 µg/mL) were analysed in triplicate, and validation was conducted for linearity, LOD, LOQ, repeatability precision, and spike-recovery accuracy (80%, 100%, and 120% levels). The method exhibited excellent linearity (y = 0.1082x + 0.0147; R² = 0.9995), with LOD and LOQ of 0.25849 µg/mL and 0.86165 µg/mL, respectively. Repeatability showed 1.40% RSD, while spike-recovery testing demonstrated high trueness (mean recovery 99.403%) with low dispersion (%RSD 0.201–0.252%). All nugget samples were negative by both qualitative screening assays. However, UV–Vis quantitative values for the nugget extracts were not available in the recorded dataset; therefore, borax-equivalent concentrations in mg/kg could not be reported for the marketed samples. Overall, the validated curcumin UV–Vis procedure demonstrates strong analytical performance and is suitable for confirmatory monitoring, provided that future surveillance applies the method directly to each sample extract to enable defensible classification as ND (LOD), LOQ, or quantified (≥LOQ).